2007
DOI: 10.1017/s0142716407070385
|View full text |Cite
|
Sign up to set email alerts
|

Gesture use in story recall by Chinese–English bilinguals

Abstract: Previous studies have shown inconsistent results concerning bilinguals' use of gestures to compensate for reduced proficiency in their second language (L2). These results could be because of differing task demands. In this study, we asked 16 intermediate English L2 speakers (whose first language [L1] was Chinese) to watch a story and tell it back in both languages. We attempted to link gesture use to proficiency while accounting for task complexity as measured by scenes recalled. The results showed that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 39 publications
(84 reference statements)
6
75
0
1
Order By: Relevance
“…In contrast to the results with iconic gestures, studies have consistently shown that bilinguals, regardless of proficiency levels, use more non-iconic gestures than iconic gestures in their weaker language (Gullberg, 1999;Marcos, 1979;Nicoladis et al, 2007;Sherman & Nicoladis, 2004). There is no theoretical connection between non-iconic gestures and lexical access (e.g., Krauss, 1998).…”
Section: Types Of Gesturesmentioning
confidence: 80%
See 2 more Smart Citations
“…In contrast to the results with iconic gestures, studies have consistently shown that bilinguals, regardless of proficiency levels, use more non-iconic gestures than iconic gestures in their weaker language (Gullberg, 1999;Marcos, 1979;Nicoladis et al, 2007;Sherman & Nicoladis, 2004). There is no theoretical connection between non-iconic gestures and lexical access (e.g., Krauss, 1998).…”
Section: Types Of Gesturesmentioning
confidence: 80%
“…Researchers have suggested various attributes that are related to gesture use such as: age (Feyereisen & Havard, 1999); gender (Brinton & Hall, 1995;Hostetter & Hopkins, 2002;Nicoladis et al, 2007); a particular language/culture (Graham & Argyle, 1975); personality traits (Wiens, Harper, & Matarazzo, 1980); motivation to learn and to perform well (McNeil & Alibali, 2001); verbal fluency (Hostetter & Alibali 2007); and cognitive skills (Alibali, 2005). However, there is no consensus on what factors are associated with individual differences in gesture use.…”
Section: Types Of Gesturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandarin was transcribed in hanyu pinyin, 1 and an English gloss was provided by the transcriber. The basic unit used to transcribe Mandarin was a word, rather than a Chinese character (see Nicoladis, Pika, Yin, & Marentette, 2007). There are many compound words in Chinese.…”
Section: Transcriptionmentioning
confidence: 99%
“…Krauss & Hadar, 1999; Mol & Kita, 2012) and macro-linguistic (e.g. Azar & Özyürek, 2016; Kendon, 1994; McNeill, 1992; McNeill & Levy, 1993; Nicoladis, Marentette, & Navarro, 2016; Nicoladis, Pika, Yin, & Marentette, 2007) levels of discourse processing. Any general claim about the relationship between speech and gesture needs to take these different levels of discourse into consideration.…”
Section: Introductionmentioning
confidence: 99%